4G LTE Network Quality and TCP/IP Performance of Telkomsel Provider in the Lolong Belanti Area - Yuhanef, Afrizal; Aulia, Siska; Pratama, Ilham Aditya; Setiawan, Herry (Brilliance: Research of Artificial Intelligence, 2023)
Lolong Belanti is one of the sub-districts in North Padang District, Padang City, West Sumatra Province. In Lolong Belanti cellular telecommunications is growing very rapidly and has become an important need for the community. Therefore, research needs to be done so that it can be a reference for providers to improve the quality and quantity of 4G LTE networks in Lolong Belanti. The measurement results on weekdays obtained the percentage of good to excellent 4G network categories have a percentage value of RSRP 99.04%, SINR 12.14% and Throughput 98.51% and the average value of download bandwidth 28.26 Mbps, upload bandwidth 23.92 Mbps, throughput 1,282,003 kbps, packet loss 0.103%, delay 5.92 ms and jitter 5.97%. While on holidays, the percentage of 4G network categories is good to very good having a percentage value of 97.91% RSRP, 12.28 SINR and 98.51% Throughput and has an average value of 13.68 Mbps download bandwidth, 17.94 Mbps upload bandwidth, 647.688 kbps Throughput, 0.26% packet loss, 17.428 ms dellay and 17.566 ms jitter.  The quality of Telkomsel's 4G LTE network provider in Lolong Belanti Village on holidays is better than on weekdays. And the comparison of TCP/IP performance for Bandwidth Download, Bandwidth Upload, Throughput and Packet Loss is superior on weekdays compared to holidays, and for Delay and Jitter is better on holidays than on weekdays.